2020
DOI: 10.1136/bmjresp-2020-000632
|View full text |Cite
|
Sign up to set email alerts
|

Endotypes identified by cluster analysis in asthmatics and non-asthmatics and their clinical characteristics at follow-up: the case-control EGEA study

Abstract: BackgroundIdentifying relevant asthma endotypes may be the first step towards improving asthma management. We aimed identifying respiratory endotypes in adults using a cluster analysis and to compare their clinical characteristics at follow-up.MethodsThe analysis was performed separately among current asthmatics (CA, n=402) and never asthmatics (NA, n=666) from the first follow-up of the French EGEA study (EGEA2). Cluster analysis jointly considered 4 demographic, 22 clinical/functional (respiratory symptoms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…A marker of oxidative stress, 8-isoprostane has also been shown to be elevated in the urine of severe asthmatics and to be worsened by smoking ( Emma et al, 2018 ). Cluster analyses of an asthma cohort have revealed subsets associated with elevated 8-isoprostane in the blood ( Nadif et al, 2020 ). Elevated hydrogen peroxide levels and 8-isoprostane can also be detected in exhaled breath condensate in asthma and are inversely correlated with lung function ( Emelyanov et al, 2001 ; Brussino et al, 2010 ).…”
Section: Nrf2 and Diseasementioning
confidence: 99%
“…A marker of oxidative stress, 8-isoprostane has also been shown to be elevated in the urine of severe asthmatics and to be worsened by smoking ( Emma et al, 2018 ). Cluster analyses of an asthma cohort have revealed subsets associated with elevated 8-isoprostane in the blood ( Nadif et al, 2020 ). Elevated hydrogen peroxide levels and 8-isoprostane can also be detected in exhaled breath condensate in asthma and are inversely correlated with lung function ( Emelyanov et al, 2001 ; Brussino et al, 2010 ).…”
Section: Nrf2 and Diseasementioning
confidence: 99%
“…Five respiratory endotypes were previously identified by cluster analysis [13] and are described in Table 1: two among never asthmatics (NA) and three among current asthmatics (CA), after taking into account a total of 23 variables for never asthmatics and 28 variables for current asthmatics. Cluster analysis jointly considered personal (age, sex, smoking status and BMI), clinical/functional (age of asthma onset, respiratory symptoms, asthma treatments, dyspnoea, skin prick tests positivity for at least one of 12 aeroallergens, current rhinitis, ever eczema, asthma attacks, hospital or emergency admission, forced expiratory volume in 1 second (FEV1) and forced vital capacity (FVC), and biological (neutrophil and eosinophil counts, total IgE and level of Fluorescent oxidation products) characteristics.…”
Section: Definition Of Respiratory Endotypesmentioning
confidence: 99%
“…[11] In the Epidemiological study on the Genetics and Environments of Asthma (EGEA), we recently identified five respiratory endotypes using cluster analysis jointly integrating asthma clinical characteristics and biomarkers related to oxidative stress and inflammation. [13] In particular, we identified among asthmatics an endotype characterized by poor lung function, respiratory symptoms, high level of fluorescent oxidation products (FlOPs, a biomarker of damages related 8 to oxidative stress), and high blood neutrophil counts. We hypothesized occupational exposure to irritants may be associated to this specific endotype.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade it has become clear that there exist several different underlying pathophysiological mechanisms, but even so, with few exceptions, almost all patients with asthma have an inflammatory infiltrate in the airways. In a recent cluster analysis of over 400 asthmatic patients, more than 85% showed type‐2 inflammation (allergic or eosinophilic) 1 …”
Section: Introductionmentioning
confidence: 99%
“…In a recent cluster analysis of over 400 asthmatic patients, more than 85% showed type-2 inflammation (allergic or eosinophilic). 1 However, inflammation does not seem to explain the full picture of asthma, and abnormal functioning of the structural cells, such as smooth muscle and epithelial cells and fibroblasts, also forms an integral part of the underlying anomalies. The pendulum swinging from asthma, thought of in the 70-80s as a reversible bronchoconstriction, to asthma thought of as a purely inflammatory disease in the 90s 2 is now considered to rest somewhere in between these two models.…”
Section: Introductionmentioning
confidence: 99%